The role of quantitative information about slip and grip force in prosthetic grasp stability. (2nd January 2018) - Damian, Dana D.; Fischer, Marco; Hernandez Arieta, Alexandro; Pfeifer, Rolf
Abstract: Prosthetic hands introduce an artificial sensorimotor interface between the prosthesis wearer and the environment that is prone to perturbations. We analyze theoretically and evaluate psychophysically the performance in stable grip control in conditions of physical grasps perturbation, such as object slip. Simulation results suggest that user-centered stable grasp control depends on two primal user parameters: reaction time to slip and grip force intensity. Experiments with human users indicate that a user's response time can be controlled by relaying information about the speed of the slipping object, while minimal grip force intensity can be adjusted with information about grip force at the onset of the slip. Based on our theoretical and experimental findings, we propose a stable grasp control method for prosthetic hands. Abstract :